2014
DOI: 10.2214/ajr.12.10359
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of T1-Weighted Gradient-Echo In-Phase Images Added to MRCP in Differentiation of Hepatolithiasis and Intrahepatic Pneumobilia

Abstract: The addition of T1-weighted gradient-echo in-phase images to standard MRCP sequences improves the detection and differentiation of hepatolithiasis and intrahepatic pneumobilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
7
1
1
Order By: Relevance
“… 19 Some investigators have reported spontaneous hyperintensity on T1-weighted images in hepatolithiasis. 20 , 21 Although a few intrahepatic stones presented high signal intensity or isosignal intensity on T1-weighted images, in our study, stones commonly appeared as intraluminal defects on low signal intensity on both T1- and T2-weighted images. These findings are consistent with the fact that low signal intensity in intrahepatic duct stones on T1- and T2-weighted images corresponded to cholesterol stones.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“… 19 Some investigators have reported spontaneous hyperintensity on T1-weighted images in hepatolithiasis. 20 , 21 Although a few intrahepatic stones presented high signal intensity or isosignal intensity on T1-weighted images, in our study, stones commonly appeared as intraluminal defects on low signal intensity on both T1- and T2-weighted images. These findings are consistent with the fact that low signal intensity in intrahepatic duct stones on T1- and T2-weighted images corresponded to cholesterol stones.…”
Section: Discussioncontrasting
confidence: 48%
“…The characteristics of intrahepatic calculi on MRI rely on their chemical composition (19). Some investigators have reported spontaneous hyper intensity on T1-weighted images in hepatolithiasis (20,21). Although a few intrahepatic stones presented high or iso signal intensity on T1 weighted images, in our study, stones commonly appeared as intraluminal defects on low signal intensity on both T1 and T2 weighted images.…”
Section: J O U R N a L P R E -P R O O F Mr Characteristicsmentioning
confidence: 44%
“…Since some gallstones are reported to be hyperintense on T1WI, T1WI in combination with T2WI can help avoid these pitfalls. 16,[32][33][34] Nevertheless, the strategy works out only for PS and some OS including paramagnetic metal chelates and usually not for CS. 17,18 Indeed, we have observed that all BC appeared distinctly positive signal on fs-T1WI; whereas, 9 out of 15 CC were faintly positive or negative signal on fs-T1WI.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use in the setting of biliary stents has not been evaluated. MRCP with T1-weighted gradient-echo in-phase images have a reported sensitivity of 98.5% to detect pneumobilia [15] and it may be used to evaluate for the loss of pneumobilia in our patient population.…”
Section: Discussionmentioning
confidence: 99%